Impact of priming on the response of neutrophils to human neutrophil alloantigen‐3a antibodies. Issue 6 (11th November 2014) - Berthold, Tom; Muschter, Stefan; Schubert, Nicole; Wesche, Jan; Ameling, Sabine; Teumer, Alexander; Reil, Angelika; Bux, Jürgen; Bakchoul, Tamam; Greinacher, Andreas
Abstract : Background: Human neutrophil alloantigen‐3a (HNA‐3a) antibodies can induce transfusion‐related acute lung injury (TRALI). The severity of TRALI varies largely among the affected patients. Severe comorbidity seems to increase the susceptibility for TRALI, potentially by priming of neutrophils. Thus, the impact of neutrophil priming on HNA‐3a antibody–mediated neutrophil aggregation and CD11b surface expression was investigated. Study Design and Methods: Neutrophils were primed using formyl‐methionyl‐leucyl‐phenylalanine (fMLP) or bacterial lipopolysaccharide (LPS). Granulocyte aggregation and CD11b surface expression were evaluated by the granulocyte agglutination test and by flow cytometry (FC), respectively. Priming‐induced changes in the surface expression of choline transporter‐like protein 2 (CTL2) and the CTL2 mRNA expression were assessed by FC and quantitative real‐time polymerase chain reaction, respectively. Results: Priming of neutrophils lowered the amount of HNA‐3a antibodies required for inducing granulocyte aggregation in a dose‐dependent manner by 50% to 75%. The priming agent concentration necessary for this response differed between donors. Priming slightly enhanced binding of HNA‐3a antibodies to neutrophils. However, CTL2 de novo synthesis was not induced after priming with LPS, indicating that increased HNA‐3a antibody binding was likely caused by translocation of intracellular CTL2 to the surface or by increased affinity of HNA‐3a antibodies to CTL2. HNA‐3a antibodies influenced CD11b surface expression on neutrophils only marginally, which was also not potentiated by priming with fMLP or LPS. Conclusion: This study provides experimental evidence supporting the "threshold model" of TRALI. Priming of neutrophils with fMLP or LPS increases their aggregation response to HNA‐3a antibodies by lowering the required antibody amount.